Potential of an andrassy and mansuli bentonite as a drilling mud material - Samsuri, Ariffin; Leyong, K. P.; Abdullah, H. (2003)
This paper presents the results of laboratory treatment works on upgrading the bentonite from two areas of Sabah, Malaysia, namely Andrassy and Mansuli for the uses in petroleum industry. Bentonite, as a common material used in water based drilling mud is the sodium bentonite. Since the Malaysian bentonite is proved to be calcium base, certain treatment is needed to convert this bentonite to sodium variety. The successfully treated bentonite will be used as a material in drilling mud, which is cheaper as compared to the Wyoming and standard bentonite. This study included two treatment processes; wet treatment and electrolysis to upgrade the non-sodium based bentonite to sodium based variety. Several sodium sources have been studied but only the sodium carbonate can successfully be used to upgrade the bentonite. The result obtained after these two treatment processes showed improvement in cation exchanger capacity (CEC), which is about 27% increment for electrolysis treament and 22% to 29% for wet treatment, respectively. However, the treated bentonite failed to meet the API 13A Specification (American Petroleum Institute)requirements for rheological properties when used as a material in drilling mud. Thereafter, certain polymer extender had been added to improve rheological of the upgraded bentonite slurry so that it can be used as a drilling mud material. In general the treated bentonite from Malaysia can be used as a replacement for the more expensive imported bentonite especially for local petroleum industry. In addition, the methods developed can also be used to convert the similar type of bentonite from other locations, since the deposits of calcium based bentonite in Malaysia are far more than the sodium based bentonite.